Developing a Passion for Learning: An Interview With Dr. David Rose. (September 2021) - Higgins, Kyle; Boone, Randall
Dr. David Rose is perhaps best known for his connection to the Center for Applied Special Technology (CAST) and as a main and driving force behind the collection of instructional, assistive, and access principles known as Universal Design for Learning (UDL). His research background includes principal investigator on National Science Foundation and U.S. Department of Education projects, and he has authored dozens of journal articles, book chapters, and books, which comprise much of the foundation for UDL.